2020
DOI: 10.32615/bp.2020.014
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physiological traits at the initial stage of Fusarium head blight infection in wheat

Abstract: Wheat (Triticum aestivum L.) is leading cereal crop worldwide, but its yield is highly affected due to various diseases, especially Fusarium head blight (FHB), which affects the metabolism of plants. The present study was conducted at the Agricultural Institute Osijek using three winter wheat cultivars (Apache, Bezostaya1, and U1) during 2016/2017. The objectives of our studies were to examine differences in physiological characteristics of FHB resistance among wheat cultivars in the early stage of infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Inoculating wheat with F. graminearum caused significant membrane deteriorations, including electrolyte leakage, lipid peroxidation, and protein oxidation, as well as H 2 O 2 accumulation and the production of hydroxyl radicals. The increased levels of stress markers in wheat that had been invaded by F. graminearum were documented by other investigations (Sorahinobar et al 2015;Spanic et al 2020;Sobhy et al 2021). Along with its function as a protective molecule against Fusarium invasion, H 2 O 2 frequently acts as an elicitor in plant-pathogen interactions (Sorahinobar et al 2017).…”
Section: Fm Min)mentioning
confidence: 70%
“…Inoculating wheat with F. graminearum caused significant membrane deteriorations, including electrolyte leakage, lipid peroxidation, and protein oxidation, as well as H 2 O 2 accumulation and the production of hydroxyl radicals. The increased levels of stress markers in wheat that had been invaded by F. graminearum were documented by other investigations (Sorahinobar et al 2015;Spanic et al 2020;Sobhy et al 2021). Along with its function as a protective molecule against Fusarium invasion, H 2 O 2 frequently acts as an elicitor in plant-pathogen interactions (Sorahinobar et al 2017).…”
Section: Fm Min)mentioning
confidence: 70%
“…SOD activity was greater in plants supplied with silicon in both cultivars from 24 to 72 hai in comparison with check plants. SOD is a key enzyme in the production of H 2 O 2 , which acts in direct defence against the pathogen, killing it, and serving as secondary messenger to alter expression of plant defence‐associated genes, and also as a substrate, for example for the POX enzymes, for cell wall reinforcement via lignification (Low & Merida, 1996; Spanic et al, 2020). POX activity increased in inoculated plants from 24 to 72 hai in cv.…”
Section: Discussionmentioning
confidence: 99%
“…Doullah et al (2006) revealed different responses of different Brassica rapa genotypes to A. brassicicola infection, also under several factors-inoculum concentration, leaf stage, and incubation temperature. Differences in Fusarium head blight (FHB) resistance connected with enzymatic activity, among wheat cultivars were described by Spanic et al (2020). The authors suggested that GPX activity, which is induced in response to pathogen invasion, might help the resistant wheat cultivar to limit infection by Fusarium species.…”
Section: Discussionmentioning
confidence: 99%